An Effective Numerical Method for Singularly Perturbed Nonlocal Boundary Value Problem on Bakhvalov Mesh (Journal of Informatics and Mathematical Sciences, 2019)
The present study focuses on obtaining an absolutely accurate computational solution of a linear singularly perturbed problem with integral boundary condition on Bakhvalov mesh. A finite difference scheme was constructed and the approximation of the presented problem was obtained. Based on the \(ε\)-perturbation parameter, it was established that the first-order uniform convergence was within the discrete maximum norm. A numerical experiment was performed in order to demonstrate the effectiveness and accuracy of the presented method. The results were confirmed through the relevant table and figures.
Keywords: Singular perturbation; Finite difference scheme; Bakhvalov mesh; Uniformly convergence; Integral boundary condition